Does a multidisciplinary team approach in a tertiary referral centre impact on the initial management of head and neck cancer?. (March 2016) - Bergamini, Cristiana; Locati, Laura; Bossi, Paolo; Granata, Roberta; Alfieri, Salvatore; Resteghini, Carlo; Imbimbo, Martina; Fallai, Carlo; Orlandi, Ester; Tana, Silvia; Iacovelli, Nicola Alessandro; Guzzo, Marco; et al.
Highlights: Multi-disciplinary team (MDT) is crucial in head and neck cancer (HNC) management. The potential impact of a MDT on HNC management has been poorly evaluated. We retrospectively analysed records of 781 HNC patients. MDT in a referral centre leads to changes in management in about 60% of patients. Summary: Objectives: A multi-disciplinary team (MDT) is essential in the management of cancer. Head and neck cancer (HNC) is a rare, complex and heterogeneous group of malignancies for which different treatment options are available. However, the potential impact of MDT on the management of HNC has been only poorly evaluated to date. This study evaluates the impact of MDT on the management of HNC in a tertiary centre. Methods: We retrospectively analysed records of HNC patients referred to a MDT evaluation at the Istituto Nazionale Tumori of Milan, Italy, from May 2007 to January 2012. All cases were reviewed by a MDT consisting of a head and neck surgeon, a radiation oncologist, and a medical oncologist. Results: Data from 781 HNC patients were analysed. Approximately 70% of patients were referred to our Institution for a second opinion consultation. Following MDT evaluation, new staging examinations were requested in 49% of patients, and treatment plan was modified in 10%. Conclusions: A MDT approach in a tertiary referral hospital leads to staging refinement of disease or changes in treatment plan in about 60% of patients.